Low-cost pick and place anthropomorphic robotic arm for the disabled and humanoid applications - Zainul Azlan, Norsinnira; Sanni, Mubeenah Titilola; Shahdad, Ifrah (Universitas Muhammadiyah Surakarta, 2020)
This paper presents the design and development of a new low cost pick and place anthropomorphic robotic arm for the disabled and humanoid applications. Anthropomorphic robotic arms are the arms that resemble human arm in terms of size, appearance and functionality. The developed robotic arm is simple, light weight and has four degrees of freedom (DOF) which are at the hand, shoulder and elbow joints. The measurement of the links are made to be close to human arm’s length. The anthropomorphic robotic arm is actuated by four DC servo motors and controlled using Arduino UNO microcontroller board. The command input for the object to be picked is driven by the voice recognition unit. The forward and inverse kinematics of the proposed new robotic arm has been analyzed and used in programming the low cost anthropomorphic robotic arm prototype to reach the desired position in the pick and place operation. The contribution of this paper is in the development of the low cost, simple and light weight anthropomorphic arm that can be easily attached with other applications such as wheel chair, and the kinematic study of the specific robot. The low cost robotic arm’s capability has been tested and the experimental result shows that it is able to perform basic pick place tasks for the disabled and humanoid applications.